2011
DOI: 10.1128/jvi.02122-10
|View full text |Cite
|
Sign up to set email alerts
|

Functional Macroautophagy Induction by Influenza A Virus without a Contribution to Major Histocompatibility Complex Class II-Restricted Presentation

Abstract: Major histocompatibility complex (MHC) class II-presented peptides can be derived from both exogenous (extracellular) and endogenous (biosynthesized) sources of antigen. Although several endogenous antigenprocessing pathways have been reported, little is known about their relative contributions to global CD4؉ T cell responses against complex antigens. Using influenza virus for this purpose, we assessed the role of macroautophagy, a process in which cytosolic proteins are delivered to the lysosome by de novo ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 74 publications
3
70
0
Order By: Relevance
“…The targeting of S1 to autophagosomes, either via S1 conjugation to LC3 or to NeoR, a model antigen, shown previously to be presented by MHCII molecules (Nimmerjahn et al, 2003), does not enhance S1-specific CD4 + T cell responses (Comber et al, 2011). In addition, shRNA knockdown of Atg7 in bone marrow-derived DC does not affect CD4+ T cell interferon-γ (IFNγ) secretion in response to S1 (Comber et al, 2011). Chaperone-mediated autophagy (CMA) is a potential alternative route that may deliver antigen to the MHCII antigen presentation pathway.…”
Section: Autophagy In Mhc Class II Antigen Presentationmentioning
confidence: 90%
See 1 more Smart Citation
“…The targeting of S1 to autophagosomes, either via S1 conjugation to LC3 or to NeoR, a model antigen, shown previously to be presented by MHCII molecules (Nimmerjahn et al, 2003), does not enhance S1-specific CD4 + T cell responses (Comber et al, 2011). In addition, shRNA knockdown of Atg7 in bone marrow-derived DC does not affect CD4+ T cell interferon-γ (IFNγ) secretion in response to S1 (Comber et al, 2011). Chaperone-mediated autophagy (CMA) is a potential alternative route that may deliver antigen to the MHCII antigen presentation pathway.…”
Section: Autophagy In Mhc Class II Antigen Presentationmentioning
confidence: 90%
“…al. have demonstrated that while autophagy is upregulated in influenza A virus infected cells, autophagy does not enhance MHCII antigen presentation of the site 1 (S1) epitope of hemagglutinin (HA) (Comber et al, 2011). The targeting of S1 to autophagosomes, either via S1 conjugation to LC3 or to NeoR, a model antigen, shown previously to be presented by MHCII molecules (Nimmerjahn et al, 2003), does not enhance S1-specific CD4 + T cell responses (Comber et al, 2011). In addition, shRNA knockdown of Atg7 in bone marrow-derived DC does not affect CD4+ T cell interferon-γ (IFNγ) secretion in response to S1 (Comber et al, 2011).…”
Section: Autophagy In Mhc Class II Antigen Presentationmentioning
confidence: 99%
“…Mice with selective impairment of autophagy in conventional DC displayed a reduced capacity to process MHC-II-restricted HSV-1 Ag (30). In contrast, alterations of autophagy in influenza-infected mouse DC or fibroblasts had no impact on the activation of influenza-specific CD4 + T cells (31). Autophagy was initially described as being involved in the processing of intracellular endogenous MHC-II Ag (19).…”
Section: A Ccumulating Evidence Suggests That Hiv-specific (Hs) Cd4mentioning
confidence: 99%
“…The transposon-derived neomycin phosphotransferase II (NeoR) gets intracellularly processed by lysosomal hydrolysis for MHC class II presentation [18]. This processing is sensitive to pharmacological macroautophagy inhibitors, and influenza hemagglutinin epitope fusion to NeoR augments MHC class II presentation of this epitope [10,18]. Interestingly, forced nuclear localization of NeoR does not compromise macroautophagy mediated processing of this antigen for MHC class II presentation [19].…”
Section: Delivery Of Intracellular Antigens For Mhc Class II Presentamentioning
confidence: 99%
“…Accordingly, LC3 can be used to deliver antigens to autophagosomes, which frequently fuse with MIICs [9]. This targeting enhances antigen presentation on MHC class II molecules up to 20fold [9,10]. A physiological condition, under which this self-antigen processing by macroautophagy seems to play a role is thymic selection.…”
Section: Delivery Of Intracellular Antigens For Mhc Class II Presentamentioning
confidence: 99%